Oxygen evolution reaction performance misjudgment caused by the self-oxidation process - Siyi Yang; Jian Luo; Yinghui Xu; Mingjie Wu; Yingkui Yang (Nano Research Energy)
Based on the interference effect of surface self-oxidation peak on the oxygen evolution reaction (OER) performance, appropriate experimental strategies and data processing methods are crucial to correctly identify and address the oxidation peak in nickel-based materials to ensure data accuracy. Considering these facts that frequent OER performance misjudgment would confuse the readers, we revealed this reason and proposed the use of multi-potential step method to avoid non-steady-state currents caused by capacitive charging effects or intermediate oxidation. Additionally, combining electrochemical impedance spectroscopy (EIS) analysis, we discussed high-frequency response characteristics to further reveal the surface self-oxidation process. These research findings are crucial for accurately evaluating the actual performance of some special materials in electrochemical catalysis.